2014
DOI: 10.1186/1756-6614-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective antioxidative effects of caffeic acid phenethyl ester (CAPE) in the thyroid and the liver are similar to those caused by melatonin

Abstract: BackgroundWhereas oxidative reactions occur in all tissues and organs, the thyroid constitutes such an organ, in which oxidative processes are indispensable for physiological functions. In turn, numerous metabolic reactions occurring in the liver create favourable conditions for huge oxidative stress. Melatonin is a well-known antioxidant with protective effects against oxidative damage perfectly documented in many tissues, the thyroid and the liver included. Caffeic acid phenethyl ester (CAPE), a component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Whereas IPA is a known auxin, melatonin is documented to act synergistically with auxins in plants [ 21 ]. These two indole substances possess significant antioxidative properties, which was confirmed in numerous experimental or clinical studies [ 6 , 9 , 10 , 11 , 14 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Whereas IPA is a known auxin, melatonin is documented to act synergistically with auxins in plants [ 21 ]. These two indole substances possess significant antioxidative properties, which was confirmed in numerous experimental or clinical studies [ 6 , 9 , 10 , 11 , 14 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 75%
“…In most studies published previously, iron was used in concentrations not exceeding the value of 300 µM to induce oxidative damage in vitro [ 9 , 10 , 11 , 14 , 15 , 22 ]. This work is the second in which we applied ferrous in extremely high concentrations, i.e., as high as 2400 µM; the first study was performed on other tissues, namely porcine thyroid and ovary [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, accumulating evidence has revealed that CAPE has antioxidant, antimicrobial, and anticancer properties [ 17 ]. As far as the antioxidant activity of CAPE is concerned, its activity is comparable to that of melatonin in thyroid and liver cells, and it significantly improves the viability of lipopolysaccharide/interferon-γ-treated RAW264.7 cells by significantly reducing the production of nitric oxide and peroxynitrite [ 18 19 ]. However, although extensive literature is available on the biological activities of CAPE, its therapeutic potential in CNS diseases is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas CAPE decreased basal LPO in a concentration-dependent manner in both tissues, melatonin did not change the basal LPO level. When antioxidants were used together with Fenton reaction substrates, they prevented – in a concentration-dependent manner and to a similar extent – experimentally- induced LPO in both tissue effects of melatonin [56]. …”
Section: Introductionmentioning
confidence: 99%